Psychological counselling. When and how? - Brunner Sciarra, Marina (2015)
Psychological counseling is important for families with a history of abortions, malformations and perinatal deaths. Comprehending bad happenings in terms of myths and beliefs is accompanied by personal or family guilt, anxiety, grief and depression. The ability to communicate, inherent to health workers, has a positive impact on both the recipient and the giver of bad news. Psychological counseling should be centered on the discussion of the thoughts that generate emotions related to important situations of life for informed future decisions.